Optimal dosing of cefotaxime and desacetylcefotaxime for critically ill paediatric patients. Can we use microsampling?. (9th June 2022) - Guerra Valero, Yarmarly C; Dorofaeff, Tavey; Coulthard, Mark G; Sparkes, Louise; Lipman, Jeffrey; Wallis, Steven C; Roberts, Jason A; Parker, Suzanne L
Abstract: Objectives: To describe the population pharmacokinetics of cefotaxime and desacetylcefotaxime in critically ill paediatric patients and provide dosing recommendations. We also sought to evaluate the use of capillary microsampling to facilitate data-rich blood sampling. Methods: Patients were recruited into a pharmacokinetic study, with cefotaxime and desacetylcefotaxime concentrations from plasma samples collected at 0, 0.5, 2, 4 and 6 h used to develop a population pharmacokinetic model using Pmetrics. Monte Carlo dosing simulations were tested using a range of estimated glomerular filtration rates (60, 100, 170 and 200 mL/min/1.73 m 2 ) and body weights (4, 10, 15, 20 and 40 kg) to achieve pharmacokinetic/pharmacodynamic (PK/PD) targets, including 100% ƒ T >MIC with an MIC breakpoint of 1 mg/L. Results: Thirty-six patients (0.2–12 years) provided 160 conventional samples for inclusion in the model. The pharmacokinetics of cefotaxime and desacetylcefotaxime were best described using one-compartmental model with first-order elimination. The clearance and volume of distribution for cefotaxime were 12.8 L/h and 39.4 L, respectively. The clearance for desacetylcefotaxime was 10.5 L/h. Standard dosing of 50 mg/kg q6h was only able to achieve the PK/PD target of 100% ƒ T >MIC in patients >10 kg and with impaired renal function or patients of 40 kg with normal renal function. Conclusions: Dosing recommendations support the use of extended or continuous infusion to achieve cefotaxime exposure suitable for bacterial killing in critically ill paediatric patients, including those with severe or deep-seated infection. An external validation of capillary microsampling demonstrated skin-prick sampling can facilitate data-rich pharmacokinetic studies.